Development of Student Worksheets (LKPD) based on the 5E Learning Cycle on the Material of Locomotor Systems in Grade XI of Senior High School - Nababan, Angelica; Martina Restuati (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study was conducted to address issues in schools, such as students' lack of understanding of the material, the use of conventional learning models, and limited use of learning media. The main goal of the research was to develop a valid, practical, and effective LKPD based on the Learning Cycle 5E model for biology lessons, specifically on the topic of the Movement System for 11th grade students at Kartika I-2 High School in Medan. This research followed the 4D development model, with data collected through observations, interviews, tests, and questionnaires.The study used several data collection instruments: teacher interview sheets, material, learning, and media validation questionnaires, teacher and student response questionnaires, and pretest and posttest questions. The results showed that the validation by material experts resulted in an average percentage of 90.6%, classified as